Social Sensitivity Improvement through Collaborative Learning Models in Islamic Religious Education - Luthfiyah, Luthfiyah; Suciani, Sri; Ruslan, Ruslan (Jurnal Tarbiyatuna, 2022)
The social awareness of students is seemingly diminishing, as indicated by the lack of care and respect for others, alongside individualism and tendencies to act emotionally and swear. These attitudes have engendered insensitive, intolerant, and uncaring behaviors amongst students. Therefore, social sensitivity is a critical attitude that should be instilled in schools. This is because education facilitates the academic, psychological, and social growth of children and ensures they become smarter, wiser, and more humane. Using a collaborative learning approach in the Islamic Religious Education discipline, the research aimed to build students' social sensitivity by activating learning activities that motivate mutual help, respect, honesty, and collaboration. The participants in this Classroom Action Research (CAR) were 24 students from class X MIA2 Senior High School State 2 Bima City. The data collection was conducted via the test approach, comprising a pre-test and post-test, and complemented by observations, interviews, and documentation. Quantitative and quantitative techniques were used to analyze the results of the primary and secondary data sources, respectively. Subsequently, the research findings indicated that the students' social sensitivity increased by 20.84% from cycle I (70.83%) to cycle II (91.67%). In the pre-test, 8 students (33.33%) showed complete learning, increasing to 13 students (54.17%) in the first cycle (I) and 21 students (87.5%) in the second cycle (II). These findings can help Islamic Religious Education teachers understand the importance of new context-based learning methodologies and models. Allowing students to explore and discuss ideas in groups can also stimulate a love of learning and increase their social awareness. As a result, classroom experience and the importance of content in everyday life can serve as the basis for students' understanding and can be directly applied in their social life.